Parental guidance and supervised learning - Alessandro Lizzeri; Marciano Siniscalchi (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2006)
We propose a simple theoretical model of supervised learning that is potentially useful to interpret a number of empirical phenomena. The model captures a basic tradeoff between sheltering the child from the consequences of his mistakes, and allowing him to learn from experience. We characterize the optimal parenting policy and its comparative-statics properties. We then show that key features of the optimal policy can be useful to interpret provocative findings from behavioral genetics
Keywords: 330; Lernen; Leistungskontrolle; Kinder; Eltern; Bildungsverhalten; Verhaltensökonomik; Schätzung; Theorie